Membangun Pemahman yang Koheren mengenai Iman Kristen kepada Generasi Milenial di Era Digital - Merfin Bengkiuk; Margareth Julia Malelak; Margarita Tenis; Marni Tauho; Yenry Anastasia Pellondou (PT. Penerbit Tiga Mutiara, 2026)
Massive digital transformation has reshaped patterns of interaction, modes of thinking, and the spiritual construction of the millennial generation, thereby creating serious challenges for the church in nurturing a mature, authentic, and contextually relevant Christian faith. The abundance of information, instant culture, and growing skepticism toward religious institutions raise a critical research problem concerning how to formulate effective strategies to develop a theologically sound understanding of faith that is also adaptive to digital culture. This study aims to construct a strategic approach that bridges faith tradition and digital dynamics through a qualitative-reflective method based on recent theological literature and critical observation of digital ministry practices. The analysis identifies four primary strategies: contextual proclamation of faith, optimization of digital platforms as spaces for testimony and education, formation of supportive online communities, and strengthening digital and theological literacy among church leaders. The findings indicate that millennials possess a deep spiritual longing but seek integrity, open dialogue, and practical relevance of faith in daily life. The study concludes that a paradigmatic transformation of church ministry is necessary by positioning digital space as a participatory and dialogical locus of spiritual formation, while the novelty of this research lies in the systematic integration of theological reflection and contextual digital pastoral strategies as an adaptive ministry model for the millennial generation in the era of technological disruption.